Performative Listening with Trees in the Sonic Ecology of Forests - Suna Başlantı (Revista Vortex)
This article reflects on the study of performative listening with trees in the sonic ecology of forests, based on a practice-based multispecies ethnography conducted in distinct forests of Turkey. By integrating the concepts from sound studies, performance studies, and posthumanist theory, I present performative listening as a method that highlights the significance of embodied, multisensory engagement with the sonic ecology of forests. Drawing on fieldwork insights, I demonstrate how performative listening can serve as a tool with potential for enhancing empathy and understanding of plant agency. This practice advocates a more inclusive approach to multispecies interactions by emphasising the transformative impact of encounters and sound